Quality Management Practices and Organizational Performance: Impact of Sustainable Product Development - Mohd Akhir Ahmad; Mohd Norhasni Asaad; Rohaizah Saad; Rosman Iteng; Mohd Kamarul Irwan Abdul Rahim (International Journal of Supply Chain Management, 2016)
Competition among the automotive industry has encouraged companies to implement quality management practices in all managerial aspects to ensure customer and stakeholder satisfactions. Fore, guaranteeing only product quality is insufficient without considering sustainable product development, which involves economic, environment, and social elements. Companies that meet both objectives gain advantages in the challenges business sustainability. This study addresses the issues regarding quality management practices, sustainable product development on organizational performance in small and medium-sized enterprises in the Malaysian automotive industry. A research was carried out in 91 SMEs automotive suppliers in throughout Malaysia. The analyzed using SPSS ver.23 has been proposed on correlation study. Specifically, this study investigates the relationship between quality management practices and organizational performance as well as the impact of sustainable product development on this relationship.